Inter-Religious Communication in Maintaining Harmony (Study of the Multi-Religious Community of Mbawa Village, Donggo District) - Sahrul, Sahrul; Wahid, Abdul; Malik, Abdul (Universitas Muhammadiyah Mataram, 2024)
Abstract: This research aims to find out how communication is used by the people of Mbawa Village to maintain harmony, and what factors cause harmony in Mbawa Village. This research uses a qualitative approach with a descriptive type of research conducting studies on natural communities. Data collection techniques by means of observation, interviews and documentation. Sampling was carried out using non-random or probability sampling, that is, not all of the population was given the opportunity to be sampled. This research shows that the people of Mbawa Village preserve three local contents as a forum for interactive communication, namely mbolo weki, tekara ne'e and rawi rasa. The factor for inter-religious harmony in Mbawa Village is the cultivation of tolerance in the right to choose the religion believed by the partner to be married or to whom he is marrying